WANITA HAMIL DI LUAR NIKAH ( STATUS ANAK ) - Maria Ulfah (Jurnal Pembaharuan Hukum, 2015)
A child born of pregnancy outside or before a legal marriage, is considered an adulterous child, can not be fathered to a father and each of them is neither inherited nor inherited. Therefore there is a marriage to cover it and the period of pregnancy has been determined, ie at least / at least six months. If the baby’s birth after the minimum period of marriage, by law the child is considered a legitimate child. Apart from that the Messenger of Allah. Also has provided that a wife who is still in the marriage contract of her husband, every child she is born, even though from the result of adultery, is considered by law is her husband’s son.